Pengaruh Jumlah Wisatawan, Jumlah Objek Wisata terhadap Pendapatan Asli Daerah Kabupaten Lombok Utara - Fathur Rahman; Wahidin Wahidin; Muhammad Dzul Fadlli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the “influence of the number of tourists, the number of tourist objects on the original revenue of North Lombok Regency in 2014-2023”. The type of research used in this study is quantitative research with an associative approach. The type of data used in this study is time series data. The data is processed using the Eviews version 10 application using the Multiple Linear Regression analysis method. The results of this study indicate that partially the independent variable Number of Tourists (X1) has a significant effect on the dependent variable, namely Regional Original Income (Y). While the variable number of tourist objects (X2) has no significant effect on local revenue (Y). The test results simultaneously Test (F) obtained that the independent variable (Number of Tourists and Number of Tourist Objects) has no significant effect on the dependent variable, namely Regional Original Income (Y) of North Lombok Regency.